Agreement Between Ti-RADS Classification and Bethesda Cytopathological Findings from Thyroid Nodules in Young Adults. - Zloczower, Elchanan; Atas, Ofir; London, Daniel; Elharar, Limor; Jacobe-Levy, Maayan; Marom, Tal (Military Medicine)
Introduction: Thyroid nodules are common in young adults. We sought to compare the sonographic characteristics (thyroid imaging reporting and data system [Ti-RADS] classification) with the reported cytological results (Bethesda categories) from thyroid nodules in young recruits and examine the efficiency of our unique multidisciplinary clinic.Materials and Methods: In this retrospective cohort, we identified young recruits (18-25 years) who underwent needle biopsies for asymptomatic thyroid nodule(s), with cytology reports of Bethesda categories II-V, performed in our "Rapid Diagnostic Service" at a large Israeli Defense Forces Medical Corps healthcare facility, between 2013 and 2018. We studied the concordance rates between their Ti-RADS and Bethesda grades, and the preoperative Bethesda grades accuracy versus final pathology results, and the time period needed for their thyroid nodules workup.Results: A total of 81 patients were included who contributed 91 nodules. A fair agreement was found between the Ti-RADS classifications and the Bethesda grades (Cohen's κ = 0.238) that was more noticeable in males than in females. The agreement rate was 87.5% in males (21 of 24), but only 77.6% in females (59 of 67) [P = .029]. Of the 5 operated benign cases, all had low Ti-RADS, and 2 had low Bethesda. Of the 8 operated malignant cases, 6 had high Ti-RADS, and 5 had high Bethesda. On average, 37.64 days elapsed between the first visit to the ultrasound study, and 24.2 days elapsed until biopsy was performed.Conclusions: Despite an overall fair agreement between the sonographic features and cytological findings in young adults, we recommend a more aggressive approach and repeated biopsies despite reported benign pathology, because of a high false-negative rate.